(untitled) (Journal of the College of Basic Education, 2024)
The idea of ​​the research is based on linking verbal composition in the tripartite system of the language to the sounds of the pronunciation itself and the extent to which the composition takes into account harmony and dissonance and its consideration of phonetic and linguistic functions and the effect of this in neglecting the pronunciation and its use. As for what exceeds the tripartite, it is included in the morphological forms of Arabic structures, whether it is abstracted from (verb) or In more detail on the different meters, the research dealt with an aspect of verbal composition in the tripartite system, with an explanation of the aspects of heaviness and dissonance in some non-triadic words that appear in the Arabic heritage.